Solvent-free electrode

By developing lithium-ion battery electrodes that do not use solvents in lithium-ion batteries, using active materials, carbon-based materials and specific polymer binding agents, and manufacturing electrodes through hot pressing, the problems of safety hazards of liquid electrolytes and poor interfacial affinity of solid electrolytes are solved, and high energy density, long life and low cost battery manufacturing is achieved.

JP2025062998APending Publication Date: 2025-04-15THE SWATCH GRP RES & DEVELONMENT LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024144303
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-08-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The liquid electrolytes in existing lithium-ion batteries have safety risks, such as the generation of lithium metal dendrites and electrolyte leakage caused by damaged battery sealing, and the poor interface affinity between the solid electrolyte and the electrode affects battery life.

Method used

A lithium-ion battery electrode without solvent was developed, using active materials, carbon-based materials and polymers with maleamide, acrylic or methacrylate groups as binding agents, and the electrode was manufactured by a hot pressing method to ensure that the interface between the electrode and the solid electrolyte was in close contact.

Benefits of technology

This technology effectively improves the mechanical strength and energy density of the battery, while extending the battery life, simplifies the manufacturing process, and reduces energy consumption and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062998000001_ABST
    Figure 2025062998000001_ABST
Patent Text Reader

Abstract

To expand battery life as compared with conventional batteries containing a liquid electrolyte and improve safety.SOLUTION: The present invention relates to a solvent-free electrode (2, 3) for a lithium-ion type battery (1). The solvent-free electrode (2, 3) includes an active material which is a source of lithium ions and capable of receiving lithium ions and / or of releasing lithium ions into its structure, and a carbon-based material to increase the electrical conductivity of the electrode. The electrode further includes a polymer with at least a maleimide group, an acrylate group or a methacrylate group, the polymer acting as a binder between the active material and the carbon-based material. Combination with a solid electrolyte having a composition similar to that of the polymer used as a binder in the electrode, without using solvents to manufacture electrodes, generates an interface between the electrodes and electrolyte materials.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solvent-free electrode and a method for producing the same, and further to a cell comprising said solvent-free electrode and optionally a solid electrolyte. [Background technology]

[0002] Conventional batteries containing liquid electrolytes, such as lithium-ion (Li-ion) batteries, have been known for several decades. However, it is known that these liquid electrolytes can have adverse effects on the safety of the battery, for example, the occurrence of lithium metal dendrites, which can lead to short circuits in the battery. Furthermore, the electrolyte can leak if the watertightness of the battery is compromised.

[0003] In recent years, solid-state electrolyte (SSE) batteries have been developed. Solid electrolytes have been used instead of liquid electrolytes in alkali or alkaline earth ion batteries (e.g., Li-ion) and in batteries with pure alkali or pure alkaline earth anodes (e.g., Li metal) because they offer a solution to the safety and leakage issues associated with liquid electrolytes. A drawback of solid electrolytes is that it is difficult to create a tight interface between the electrode and the electrolyte, which can result in reduced battery life.

[0004] At the same time, all-solid-state batteries containing solvent-free electrodes are being developed to extend battery life and develop safer batteries. Eliminating the most commonly used solvent in electrode formulations, NMP (N-methyl-2-pyrrolidone), can reduce the total energy consumed during production by 47%. The presence of solvents requires high-temperature debinding, which results in energy losses, but solvents such as NMP, which are highly toxic and harmful to health, cannot be completely removed. Water can solve the toxicity problem without the cost of recycling the solvent, but the production of thick electrodes with high energy density and good mechanical strength remains a challenge. Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to overcome the above mentioned drawbacks by developing a solvent-free electrode that has good mechanical strength and high energy density, while at the same time being able to form an intimate interface with the solid electrolyte.

[0006] More specifically, the invention consists in producing a solvent-free electrode comprising an active material, the material being a source or acceptor of lithium ions, a carbon-based material to improve the electrical conductivity of the electrode, and a polymer intended to bond the active material and the carbon-based material. Advantageously, the electrode consists only of the active material, the carbon-based material, and the polymer. [Means for solving the problem]

[0007] The new electrode formulation does not use any solvents in the manufacturing of the electrodes, which simplifies manufacturing and reduces production costs.

[0008] Combining a solid electrolyte with a similar composition to the polymer used as the binder in the electrode ensures tight contact at the interface between the electrode and electrolyte material, thereby extending the battery's lifespan and improving its performance.

[0009] More specifically, the present invention provides a solventless electrode for a lithium-ion type battery, comprising: - an active material that is a source of lithium ions and is capable of receiving and / or releasing lithium ions into its structure - Carbon-based materials that improve the conductivity of electrodes wherein the electrode further comprises a polymer having at least a maleimide group, an acrylate group, or a methacrylate group, the polymer acting as a binder between the active material and the carbon-based material.

[0010] According to alternative embodiments of the invention, the electrodes have one or more of the following features: - the polymer further comprises an alkali metal salt and / or an alkaline earth metal salt said at least maleimide group, acrylate group, or methacrylate group being a terminal group; - the polymer comprises at least one maleimide group and a lithium or sodium salt - Active materials are LiFePO4, LiNiMnCoO2, LiCoO2, Li4Ti5O 12 or graphite, and the carbon-based material includes activated carbon, carbon black, and / or graphite. The electrode comprises, by weight, 50-80%, preferably 60-75%, of active material, 0.5-5%, preferably 1-4%, of carbon-based material, and 10-45%, preferably 20-35%, of polymer. said polymer being obtained from a polymerizable composition comprising: A first polymer comprising a first portion and a second portion, the first portion being capable of coordinating alkali metal cations and / or alkaline earth metal cations, and the second portion being photoactivatable and / or thermally activatable. Oligomers having at least two photoactivatable and / or thermally activatable groups a second polymer comprising a third portion, the third portion comprising an alkali metal salt or an alkaline earth metal salt; Plasticizers A polymerization initiator for initiating the polymerization of the second portion of the first polymer with the photoactivatable and / or thermally activatable groups of the oligomer under the effect of a temperature of 20 to 150° C. or under the effect of irradiation. a second moiety, and one or more photoactivatable and / or thermally activatable groups that are maleimide groups, acrylate groups, or methacrylate groups; The polymerizable composition comprises, based on the total weight of the polymerizable composition, 10 to 50% by weight of a first polymer, 1 to 20% by weight of an oligomer, 1 to 20% by weight of a second polymer, 20 to 60% by weight of a plasticizer, and 0.01 to 2% by weight of a polymerization initiator. The polymerizable composition further comprises 0.5 to 5 wt. % of an alkali metal salt and / or an alkaline earth metal salt, based on the total weight of the polymerizable composition. The first part of the polymerizable composition comprises a polyethylene oxide part.

[0011] As used in this disclosure, the term "photoactivatable" includes components, molecules, groups, or moieties that can be activated under the influence of radiation, such as, but not limited to, ultraviolet (UV) radiation, infrared (IR) radiation, visible light radiation, or combinations thereof.

[0012] The term "thermally activatable" as used in the present disclosure includes components, molecules, groups, or moieties that can be activated by a change in temperature. Specifically, the temperature change is heating. Advantageously, the activation temperature is between 20 and 150°C, preferably between 25 and 100°C.

[0013] Activation by heat and / or radiation includes, but is not limited to, activation for oligomerization, polymerization, or crosslinking, and / or activation for initiation of oligomerization, polymerization, or crosslinking.

[0014] An "end group" is considered to be a group present at one end of a polymer (chain).

[0015] As used in this disclosure, a "telechelic oligomer" is considered to be an oligomer that is capable of subsequent polymerization due to the presence of at least one reactive group at each of the ends of the oligomer (chain).

[0016] A second aspect of the invention relates to a cell comprising, as at least one of the two electrodes, a solvent-free electrode as described above.

[0017] Advantageously, said cell further comprises a solid electrolyte made from said polymer having at least maleimide, acrylate or methacrylate groups.

[0018] A third aspect of the present invention relates to a method for producing a solvent-free electrode as described above, the method comprising the steps of: - polymerizing the polymerizable composition as described above to obtain a polymer having at least maleimide groups, acrylate groups, or methacrylate groups. - mixing said polymer with a powder of active material and a powder of carbon-based material; - hot pressing the resulting mixture to produce an electrode.

[0019] Advantageously, the polymer is ground to obtain a powder before the mixing step. Alternatively, after the mixing step and before the pressing step, the mixture is ground, preferably under a nitrogen atmosphere.

[0020] Advantageously, pressing is carried out at a temperature between 90 and 150° C., preferably between 100 and 140° C., with a force between 5 and 25 kN, preferably between 10 and 20 kN, for a period of 1 to 20 minutes, preferably between 3 and 10 minutes.

[0021] Advantageously, the pressing is carried out between a sheet acting as a separator and a current collector.

[0022] The drawings depict non-limiting embodiments of the present invention, illustrating the objects, advantages and features of the present invention. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 shows a first portion which is a component of a polymerizable composition. [Diagram 2] FIG. 2 shows a second part which is a component of a polymerizable composition. [Diagram 3] FIG. 1 illustrates a first component of a polymerizable composition. [Figure 4] FIG. 2 illustrates a second component of the polymerizable composition. [Diagram 5] FIG. 2 illustrates a third component of the polymerizable composition. [Figure 6] FIG. 1 illustrates components of a battery, particularly a cell battery. [Figure 7] FIG. 1 illustrates a solvent-free electrode according to the present invention. [Figure 8] 1 is a graph showing the areal capacity of cells including electrodes according to the present invention as a function of the number of charge / discharge cycles. [Figure 9] 1 is a graph showing voltage and current as a function of time for various cycles for a cell including an electrode according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention relates to a solvent-free electrode comprising an active material, a carbon-based material, and a polymer acting as a binder between the active material and the carbon-based material. Preferably, the electrode consists of an active material, a carbon-based material, and a polymer acting as a binder.

[0025] The active material is a source of lithium ions and is capable of receiving and / or releasing lithium ions into its structure. Preferably, the active material is LiFePO4, LiNiMnCoO2, LiCoO2, Li4Ti5O 12 , and graphite. In the positive electrode, the active material is a source of lithium ions, and therefore participates in the capacity of the electrode and can receive lithium ions in its structure. In the negative electrode, the active material can receive or release lithium ions in its structure by intercalation. The active material is more specifically LiFePO4, LiNiMnCoO2, or LiCoO2 in the positive electrode and more specifically Li4Ti5O 12 Or graphite.

[0026] The purpose of the carbon-based material is to improve the electrical conductivity of the electrode, and preferably comprises or consists of activated carbon, carbon black, and / or graphite.

[0027] The binder polymer comprises at least a maleimide group, an acrylate group, or a methacrylate group. Preferably, the maleimide group, the acrylate group, or the methacrylate group is a terminal group. Preferably, there are two maleimide groups, one at each end. Preferably, there is at least one maleimide group.

[0028] Preferably, the polymer further comprises an alkali metal salt and / or an alkaline earth metal salt. Preferably, this is a lithium or sodium salt. More preferably, this is a lithium salt. Preferably, the polymer comprises at least a maleimide group and a lithium or sodium salt, more preferably a lithium salt.

[0029] The electrode comprises, by weight, 50-80%, preferably 60-75%, active material, 0.5-5%, preferably 1-4%, carbon-based material, and 10-45%, preferably 20-35%, polymer.

[0030] The polymer is derived from a polymerizable composition comprising: - a first polymer comprising a first portion and a second portion, the first portion being capable of coordinating an alkali metal cation and / or an alkaline earth metal cation, and the second portion being photoactivatable and / or thermally activatable. - an oligomer having at least two photoactivatable and / or thermally activatable groups a second polymer comprising a third portion, the third portion comprising an alkali metal salt or an alkaline earth metal salt. - Plasticizers - a polymerization initiator for initiating the polymerization of the second portion of the first polymer with the photoactivatable and / or heatactivatable groups of the oligomer under the effect of a temperature of 20-150°C or under the effect of irradiation. a second moiety and one or more of a photoactivatable and / or thermally activatable group which is a maleimide group, an acrylate group, or a methacrylate group.

[0031] The first portion of the first polymer of the polymerizable composition according to the invention is capable of coordinating alkali metal cations and / or alkaline earth metal cations, advantageously alkali metal cations and / or alkaline earth metal cations in the electrode according to the invention. That is, the first portion is advantageously selected to ensure ionic conductivity in the electrode. Non-limiting examples of the first portion are the polyethylene oxide (PEO) portion and the polyethylene glycol (PEG) portion shown in FIG. 1. Advantageously, in FIG. 1, u represents the repeat number and is selected from 20 to 80, preferably 30 to 70, more preferably 40 to 60, for example 50 to 55.

[0032] The second portion of the first polymer of the polymerizable composition according to the present invention is a portion provided to allow polymerization of the polymerizable composition. Thus, the second portion is photoactivatable and / or thermally activatable. Non-limiting examples are the maleimide portion, the acrylate portion, and the methacrylate portion shown in FIG. 2.

[0033] Advantageously, the first polymer has a molar mass between 1000 and 5000 g / mol, preferably between 1500 and 4000 g / mol, for example between 2000 and 3000 g / mol, more preferably between 2250 and 2750 g / mol, for example between 2350 and 2600 g / mol.

[0034] Advantageously, the first polymer comprises 0.1 to 0.7 mEq (milliequivalent), preferably 0.2 to 0.6 mEq, more preferably 0.3 to 0.5 mEq, for example 0.35 to 0.45 mEq, or 0.4 mEq of the second portion per gram of first polymer.

[0035] Specific examples of the first polymer include α-methoxy-ω-maleimide polyethylene oxide, polyethylene glycol methacrylate (PEGMA), and α-methoxy-ω-maleimide polyethylene glycol, as shown in FIG.

[0036] Advantageously, the polymerizable composition contains from 10 to 50% by weight, preferably from 12 to 45% by weight, for example from 15 to 40% by weight, of the first polymer, based on the total weight of the polymerizable composition.

[0037] The polymerizable composition also contains an oligomer. The oligomer has at least two photoactivatable groups and / or heat-activatable groups. These groups can be polymerized with the second part of the first polymer and / or the third part of the second polymer. Preferably, the group of the oligomer can be polymerized with at least the third part of the second polymer. The photoactivatable group and / or heat-activatable group can be, but is not limited to, a maleimide group, an acrylate group, and a methacrylate group.

[0038] Advantageously, the oligomer comprises from 0.1 to 0.7 mEq (milliequivalents), preferably from 0.2 to 0.9 mEq, more preferably from 0.3 to 0.8 mEq, for example from 0.4 to 0.7 mEq, or from 0.5 to 0.6 mEq of photoactivatable and / or heat activatable groups per gram of oligomer.

[0039] An example of an oligomer is PPG-block-PEG-block-PPG,α,ω-bis(maleimide) shown in Figure 4, which is a polyethylene oxide-polypropylene oxide (PEO-PPO) with a maleimide group at each end of the chain. Advantageously, x+z is between 2 and 20, preferably between 5 and 15, more preferably between 6 and 12, for example between 8 and 9. Advantageously, y is between 20 and 100, preferably between 40 and 80, more preferably between 50 and 75, for example between 60 and 70, or between 62 and 67.

[0040] Another example of an oligomer is polyethylene glycol (PEG) with a methacrylate group (MA) at each end of the chain (PEG-DiMA).

[0041] Advantageously, the oligomer has a molar mass between 250 and 10,000 g / mol, preferably between 500 and 5,000 g / mol, more preferably between 750 and 4,000 g / mol, for example between 1,000 and 3,750 g / mol, or even between 2,000 and 3,600 g / mol.

[0042] Advantageously, the polymerizable composition contains from 1 to 20% by weight, preferably from 2 to 15% by weight, for example from 3 to 15% by weight, of oligomer, based on the total weight of the polymerizable composition.

[0043] Advantageously, the oligomer has at least one photoactivatable and / or thermally activatable group at each end of the oligomer chain, in which case the oligomer is a telechelic oligomer. The addition of the telechelic oligomer to the polymerizable composition allows for better control of the polymerization and thus the structure of the resulting polymer network. Advantageously, the polymer network is a linear polymer network. Moreover, the chain between the two bond points of the polymerized composition thus obtained is sufficiently long, so that the polymerized composition is rather "loose" and the electrode has good ionic conductivity.

[0044] Advantageously, the oligomer may act as a plasticizer and / or as an enhancer of the ionic conductivity of the electrode.

[0045] The second polymer of the polymerizable composition comprises a third portion. Advantageously, the third portion comprises a salt of an alkali metal and / or a salt of an alkaline earth metal. Advantageously, the alkali metal comprises lithium, sodium, potassium, or a combination thereof. Preferably, the alkali metal is lithium. Advantageously, the alkaline earth metal comprises magnesium, beryllium, calcium, or a combination thereof. Preferably, the alkaline earth metal is magnesium.

[0046] Advantageously, the third moiety is capable of providing alkali metal cations and / or alkaline earth metal cations in the electrode. Advantageously, the alkali metal cations and / or alkaline earth metal cations are capable of migrating along the first polymer and oligomer in the electrode. This migrating influences the ionic conductivity of the electrode. Furthermore, the third moiety incorporated in the chain of the second polymer also makes it possible to reduce the mobility of the alkali metal counter anions and / or the mobility of the alkaline earth metal counter anions in the electrode, thereby making it possible to improve the mobility of the alkali metals and / or the alkaline earth metals.

[0047] FIG. 5 shows an example of a second polymer of a polymerizable composition according to the present invention, where the third moiety is lithium bis(trifluoromethane)sulfimide (LiSTFSI, CAS number: 210226-98-5).

[0048] Advantageously, the polymerizable composition contains from 1 to 20% by weight, preferably from 2 to 15% by weight, for example from 5 to 10% by weight, of the second polymer, based on the total weight of the polymerizable composition.

[0049] A plasticizer in a polymerizable composition can advantageously solubilize the components of the composition. An example of a plasticizer includes, but is not limited to, propylene carbonate.

[0050] Advantageously, the polymerizable composition contains 20 to 60% by weight, preferably 25 to 55% by weight, for example 30 to 50% by weight, of plasticizer, based on the total weight of the polymerizable composition.

[0051] The composition further comprises a polymerization initiator, which makes it possible to initiate the polymerization between the second part of the first polymer, the photoactivatable and / or heatactivatable groups of the oligomer and the third part of the second polymer. The initiation of the polymerization and / or the polymerization itself is carried out under the influence of a temperature of 20 to 200° C., preferably 20 to 150° C., more preferably 25 to 100° C., for example 30 to 80° C., or under the influence of irradiation. Advantageously, the irradiation comprises one or more of UV irradiation, IR irradiation and visible light (VIS) irradiation.

[0052] If the polymerization step is carried out under the influence of irradiation, preferably UV irradiation, it is carried out for a period of 5 seconds to 20 minutes, such as 10 seconds to 15 minutes, preferably 20 seconds to 10 minutes, more preferably 30 seconds to 5 minutes, such as 4 minutes, 3 minutes, 2 minutes, 1 minute, 55 seconds, 50 seconds or 45 seconds.

[0053] When the polymerization is carried out under the influence of temperature, it is carried out for 1 minute to 5 hours, preferably 5 minutes to 4 hours, for example 10 minutes to 3 hours, 20 minutes to 2.5 hours, or 30 minutes to 2 hours.

[0054] Advantageously, the polymerization initiator is radical in nature. This means that in the present disclosure, the polymerization initiator can release radicals under the influence of temperature or irradiation as described above. These radicals then initiate polymerization between the first polymer, the second polymer, and the oligomer of the composition.

[0055] Examples of polymerization initiators include, but are not limited to, 2,2'-azobis(isobutyronitrile) (AIBN) and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (CAS number: 106797-53-9).

[0056] Advantageously, the polymerizable composition contains 0.01 to 2% by weight, preferably 0.1 to 1.5% by weight, for example 0.25 to 1% by weight, of polymerization initiator, based on the total weight of the polymerizable composition.

[0057] The polymerizable composition may also contain an alkali metal salt and / or an alkaline earth metal salt. Advantageously, the alkali metal salt contains or consists essentially of a lithium salt. Advantageously, the alkaline earth metal salt contains or consists essentially of a magnesium salt. Non-limiting examples of salts include lithium bis(fluorosulfonyl)imide (LIFSI) and lithium bis(trifluoromethanesulfonyl)imide (LITFSI).

[0058] The inventors have surprisingly discovered that the addition of an alkali metal salt and / or an alkaline earth metal salt to a polymerizable composition improves ionic conductivity compared to electrodes made with polymers derived from compositions without the addition of an alkali metal salt and / or an alkaline earth metal salt. The inventors believe that the improved conductivity is achieved by a synergistic effect between the salt of the third portion of the second polymer and another salt added to the composition.

[0059] Advantageously, when the polymerizable composition comprises an alkali metal salt and / or an alkaline earth metal salt, the composition contains from 0.5 to 5% by weight, preferably from 0.75 to 4% by weight, for example from 1 to 3% by weight, of the salt, based on the total weight of the polymerizable composition.

[0060] The polymer acting as a binder between the active material and the carbon-based material is obtained by polymerization of the polymerizable composition according to the present disclosure. The electrode is manufactured by extrusion or hot pressing using this polymer obtained by polymerization of the polymerizable composition. Here, the manufacturing method by hot pressing is more specifically described (FIG. 7). This method includes the following steps: - polymerizing said polymerizable composition to obtain a polymer having at least maleimide groups, acrylate groups, or methacrylate groups. - mixing the polymer with a powder of active material and a powder of carbon-based material; hot pressing the mixture 11 obtained to produce the electrodes 2, 3.

[0061] Advantageously, the polymer is ground before being mixed with the other powder. Alternatively, the mixture comprising the polymer and the other two powders is ground before polymerization.

[0062] Advantageously, the method comprises the additional step of freezing the polymer or the mixture prior to the grinding step to render the polymer brittle, this step being carried out, for example, under a nitrogen atmosphere.

[0063] The pressing is carried out at a temperature of 90 to 150° C., preferably 100 to 140° C., with a force of 5 to 25 kN, preferably 10 to 20 kN, for 1 to 20 minutes, preferably 3 to 10 minutes.

[0064] Advantageously, the pressing is performed between a sheet 9 and a current collector 10. The sheet can be an integral part of the resulting electrode, can be removed or can fall off naturally while retaining a functional electrode. For example, the sheet can be a cellulose sheet acting as a separator and the current collector can be made of aluminum or an aluminum alloy.

[0065] The present disclosure further relates to cells comprising the solvent-free electrodes according to the invention. Figure 6 shows an example of a cell 1. It has a button cell configuration known in the art as a CR2032 type configuration.

[0066] The cell 1 comprises an anode 2 and a cathode 3, at least one of which is made with a formulation according to the invention. Advantageously, the cell 1 further comprises a solid polymer electrolyte 4 between the anode 2 and the cathode 3, made with the polymerizable composition described above.

[0067] Advantageously, the cell 1 further comprises a button cell cover 5, a button cell base 6, a spacer 7 and a spring 8. The spacer 7 and the spring 8 ensure good contact between the other components 2, 3, 4, 5, 6 of the cell 1, respectively.

[0068] The performance of a cell containing a positive electrode according to the invention, having as active materials 70% by weight LiFePO4, 28% by weight of a polymer containing maleimide groups, and 2% by weight of carbon black, was tested. The positive electrode was prepared by mixing different powders and pressing it between a cellulose sheet and an aluminum current collector at a pressure of 15 kN and a temperature of 120°C for 5 minutes.

[0069] The theoretical capacity of the positive electrode is 1.25 mAh / cm 3 Commercially available Li4Ti5O 12 (LTO) anode and was mounted in a battery containing a standard liquid electrolyte (LP30).

[0070] The cell's lifetime was tested over 30 charge / discharge cycles between 1.5 and 2.4 V, with the first 10 cycles shown in Figure 9. The cycle rate for LTO was C / 16, which corresponds to a charge of 0.140 mA. Charging was performed with a constant current and discharging was performed with the same current in the reverse direction. For each cycle, the cell was charged to 100% state of charge and discharged to 100% depth of discharge.

[0071] The results for the two samples are shown in the graph of Figure 8, which plots areal capacity as a function of cycle number. From Figure 8, it can be seen that the loss of areal capacity after 30 cycles is less than 25% compared to the areal capacity of the first cycle, and the capacity stabilizes after about 15 cycles. Thus, the battery has excellent capacity stability, i.e., long life. [Explanation of symbols]

[0072] 1 cell 2 negative electrode 3 Positive electrode 4. Solid polymer electrolyte 5 Button Cell Cover 6 Button Cell Base 7 Spacer 8. Spring 9 Sheets 10 Current collector 11 mixture u Number of repetitions

Claims

1. A solvent-free electrode (2, 3) for a lithium-ion type battery, comprising: an active material that is a source of lithium ions and is capable of receiving and / or releasing lithium ions into its structure; a carbon-based material that improves the electrical conductivity of the electrodes (2, 3); wherein the electrode further comprises a polymer having at least a maleimide group, an acrylate group, or a methacrylate group, the polymer acting as a binder between the active material and the carbon-based material.

2. 2. Solvent-free electrode (2, 3) according to claim 1, characterized in that the polymer further comprises a salt of an alkali metal and / or an alkaline earth metal.

3. 2. A solvent-free electrode (2, 3) according to claim 1, characterised in that the at least one maleimide, acrylate or methacrylate group is a terminal group.

4. 4. Solvent-free electrode (2, 3) according to claim 2 or 3, characterized in that the polymer comprises at least one maleimide group and a lithium or sodium salt.

5. The active material is LiFePO 4 , LiNiMnCoO 2 , LiCoO 2 , Li 4 Ti 5 O 12 2. The solvent-free electrode (2, 3) according to claim 1, characterized in that the carbon-based material comprises activated carbon, carbon black, and / or graphite.

6. 2. Solvent-free electrode (2, 3) according to claim 1, characterized in that it comprises, in percentage by weight, 50-80%, preferably 60-75%, of active material, 0.5-5%, preferably 1-4%, of carbon-based material and 10-45%, preferably 20-35%, of polymer.

7. The polymer is a first polymer comprising a first portion and a second portion, said first portion being capable of coordinating alkali metal cations and / or alkaline earth metal cations, and said second portion being photoactivatable and / or thermally activatable; - oligomers carrying at least two photoactivatable and / or thermally activatable groups a second polymer comprising a third portion, said third portion comprising a salt of an alkali metal or an alkaline earth metal; - Plasticizers a polymerization initiator for initiating the polymerization of the second portion of the first polymer with the photoactivatable and / or thermally activatable groups of the oligomer under the effect of a temperature between 20 and 150° C. or under the effect of irradiation; a second portion and one or more of the photoactivatable and / or thermally activatable groups being maleimide groups, acrylate groups, or methacrylate groups; 2. Solvent-free electrode (2, 3) according to claim 1, characterized in that it is obtained from a polymerizable composition comprising:

8. The solvent-free electrode (2, 3) according to claim 7, characterized in that the polymerizable composition comprises, based on the total weight of the polymerizable composition, 10 to 50% by weight of the first polymer, 1 to 20% by weight of the oligomer, 1 to 20% by weight of the second polymer, 20 to 60% by weight of the plasticizer, and 0.01 to 2% by weight of the polymerization initiator.

9. The solvent-free electrode (2, 3) according to claim 7 or 8, characterized in that the polymerizable composition further comprises 0.5 to 5 wt. % of an alkali metal salt and / or an alkaline earth metal salt, based on the total weight of the polymerizable composition.

10. 8. Solvent-free electrode (2,3) according to claim 7, characterized in that said first part of said polymerizable composition comprises a polyethylene oxide part.

11. A cell (1) comprising, for at least one of said two electrodes (2, 3), a solvent-free electrode (2, 3) according to claim 1.

12. 12. The cell (1) of claim 11, further comprising a solid electrolyte made from said polymer having at least maleimide, acrylate, or methacrylate groups.

13. A method for producing a solvent-free electrode (2, 3) according to claim 1, comprising the steps of: - polymerizing the polymerizable composition according to claim 7 to obtain said polymer having at least maleimide, acrylate or methacrylate groups. - mixing said polymer with a powder of active material and a powder of carbon-based material; - hot pressing the mixture (11) obtained to produce said electrodes (2, 3) A method for producing a solvent-free electrode (2, 3) according to claim 1, comprising:

14. Method for producing a solvent-free electrode (2, 3) according to claim 13, characterized in that the pressing is carried out at a temperature of 90-150°C, preferably 100-140°C, with a force of 5-25 kN, preferably 10-20 kN, for a period of 1-20 minutes, preferably 3-10 minutes.

15. A method for producing a solvent-free electrode (2, 3) according to claim 13 or 14, characterized in that the mixture (11) is pressed between a sheet (9) and a current collector (10).

16. Method for producing a solvent-free electrode (2, 3) according to claim 13, characterized in that the polymer is ground before or after the mixing step.

Citation Information

Patent Citations

  • Polymer single-ion electrolyte and preparation method thereof

    CN103509153A

  • Lithium secondary battery negative electrode mixture, lithium secondary battery negative electrode, and lithium secondary battery

    JP2011076743A

  • Binder for all-solid-state secondary batteries, and all-solid-state secondary battery

    WO2017047379A1